Do hypomethylating agents prevent relapse after Allo‐HCT?. Issue 1 (29th November 2018) - Schroeder, Thomas; Rautenberg, Christina; Haas, Rainer; Germing, Ulrich; Kobbe, Guido
Abstract: Relapse is the main cause of treatment failure in patients with acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) and limits the curative potential of allogeneic blood stem cell transplantation (allo‐HCT). Many patients can either not tolerate or do not achieve durable remissions through commonly used treatment options such as salvage chemotherapy, donor lymphocyte infusions (DLI), and/or second transplants. Thus, patients who relapse after allo‐HCT have a very poor prognosis with the currently available therapies implicating the great medical need for relapse prevention. After having demonstrated efficacy and tolerability as salvage therapy in patients with myeloid malignancies who relapse after allo‐HCT the hypomethylating agents azacitidine (Aza) and decitabine (DAC) have also been tested as prophylactic and preemptive approaches in patients with AML and MDS after allo‐SCT. Here, we summarize the current literature reporting on results from prospective trials and retrospective analyses regarding the prophylactic and preemptive use of Aza and DAC after allo‐SCT and aim to give an answer if these hypomethylating agents (HMA) are able to prevent relapse of myeloid malignancies after allo‐HCT.